Relationship between job satisfaction and decent treatment gives the nurse the patient to go to a private health facility level IV care Lima - 2013 - Casildo Bedón, Danitza Raquel (2019)
Objective: To establish the relationship between job satisfaction and decent treatment provides professionalnursing patient who attends a private institution level IV health care in the city of Lima. Methodology: Thestudy was non-experimental design; quantitative, descriptive, correlational and cross-sectional. The studypopulation consisted of 57 nursing professionals working in the health care area of San Felipe Clinic during thepast year. In data collection Two measuring instruments used for job satisfaction variable is adapted and modifiedRobbins questionnaire developed in 2000; Variable dignified treatment for an observation guide developed bythe researcher with reference to the quality indicator survey by the National Crusade quality health services wasused. To establish the relationship between the variables statistical Spearman Rho correlation (rs) was used.Results: We showed that job satisfaction had no significant relationship with dignity; according to SpearmanRho test 0.042 and p = 0.758 value. Nature of work content and dignified treatment variable that providesprofessional nursing: Though a significant positive correlation was found for the dimension. Conclusion: Thereis no significant correlation between job satisfaction and decent treatment provides professional nursing.